Redefine Hyperprogressive Disease During Treatment With Immune-Checkpoint Inhibitors in Patients With Gastrointestinal Cancer - Wang, Zhenghang; Liu, Chang; Bai, Yuezong; Zhao, Xiaochen; Cui, Longgang; Peng, Zhi; Zhang, Xiaotian; Wang, Xicheng; Zhao, Zhengyi; Li, Jian; Shen, Lin (Frontiers in Oncology, 2021)
Objective：Emerging evidence showed that immune checkpoint inhibitors (ICIs) lead to hyperprogressive disease (HPD) in a small proportion of patients. There is no well-recognized standard for the evaluation of HPD. Comprehensive exploration of HPD definition system in gastrointestinal cancer treated with ICI is lacking to date. Methods: A total of 126 patients with advanced or metastatic gastrointestinal cancer treated with ICI monotherapy were analyzed. Seven definitions of HPD were defined with tumor growth kinetics (TGK) or tumor growth rate (TGR) by including new lesions or not, and with different cutoffs. Incidence and performance of different criteria were compared. Clinicopathologic characteristics and baseline genomic variations associated with HPD were also explored. Results: Tumor growth kinetics ratio of more than 2 folds that incorporated new lesions into calculation of HPD outperformed other definitions by successfully stratifying fourteen patients (11.1%) with both accelerated disease progression (median PFS, 1.62 versus 1.93 months; hazard ratio, 1.85; 95%CI, 0.98 to 3.48; P = 0.059) and worse overall survival (median OS, 3.97 versus 10.23 months; hazard ratio, 2.30; 95%CI, 1.11 to 4.78; P = 0.021). Baseline genomic alterations in circulating tumor DNA, including SMARCA2, MSH6, APC signaling pathway and Wnt signaling pathway might be associated with the risk of HPD. Conclusion: Incorporating new lesions emerging during the treatment was shown to be reliable for the assessment of TGK. TGK serves as a more convenient way to reflect tumor growth acceleration compared with TGR. Genomic alterations were suggested to be associated with the occurrence of HPD.